PENGARUH ORIENTASI PASAR DAN JARINGAN TERHADAP KINERJA UMKM DI KECAMATAN LARANGAN KABUPATEN BREBES - Handayani, Sri Ratih; ', Apriyani; Prasetya, Avin Dwi (Jurnal Strategik, 2025)
This study takes the title of the influence of market orientation and network on the performance of MSMEs in Larangan District, Brebes Regency. The formulation of the problem is as follows: 1. How do market orientation and network partially influence the performance of MSMEs in Larangan District, Brebes Regency? 2. How do market orientation and network simultaneously influence the performance of MSMEs in Larangan District, Brebes Regency? 3. Which variable has a dominant influence on the performance of MSMEs in Larangan District, Brebes Regency? The objectives of the study are as follows: 1. To determine the influence of market orientation and network partially on the performance of MSMEs in Larangan District, Brebes Regency? 2. To determine the influence of market orientation and network simultaneously on the performance of MSMEs in Larangan District, Brebes Regency? 3. To determine the variables that have a dominant influence on MSMEs in Larangan District, Brebes Regency? The hypothesis is a temporary assumption or temporary answer to the formulation of the problem whose truth still has to be proven. The following are the hypotheses that: 1. Market Orientation and Network have a partial effect on the performance of MSMEs in Larangan District, Brebes Regency. 2. Market Orientation and Network have a simultaneous effect on the performance of MSMEs in Larangan District, Brebes Regency. 3. The Market Orientation variable has a dominant effect on the performance of MSMEs in Larangan District, Brebes Regency.The research method used is a case study on MSMEs in Larangan District, Brebes Regency, while the data collection methods used are surveys, interviews, questionnaires, and library research. The analysis I used is a validity test, a reliability test, multiple linear regression analysis, a classical assumption test consisting of a Multicollinearity Test, an Autocorrelation Test, a Heteroscedasticity Test, a Normality Test, and a Hypothesis Test, namely the t-test, the f-test, and the coefficient of determination (R2) test.From the analysis results, it can be concluded:1.    The results of the partial regression coefficient test at a confidence level of 73.50% (a = 0.05) and degrees of freedom (2) (73) on the market orientation variable (X1) obtained a calculated t of while the t table was 11.943 so the calculated t> t table thus the null hypothesis is rejected and the alternative hypothesis is accepted, meaning the Market Orientation variable (X1) has a positive influence on the performance of MSMEs (Y) and for the Network variable (X2) obtained a calculated t of 6.684 while the t table was 1.666 so the calculated t> t table thus the null hypothesis is rejected and the alternative hypothesis is accepted, meaning the Network variable (X2) has a positive influence on the performance of MSMEs (Y). Thus the first hypothesis is declared proven.2.    Together, the market orientation variables (X1) and network (X2) have an influence on the performance of MSMEs (Y), this is proven by the F count value of 96.844>F table 3.13. Thus, it can be said that the market orientation variables (X1) and network (X2) simultaneously have a positive influence on the performance of MSMEs (Y). Thus, the second hypothesis is declared proven.3.    The market orientation variable (X1) has an influence on MSME performance (Y), this is indicated by the partial regression coefficient value of the market orientation variable of 0.463 which is greater than the regression coefficient value of the Network variable (X2) of 0.188. Thus, the third hypothesis states that the Market Orientation variable has a dominant influence on employee performance (Y). Thus, the third hypothesis is declared proven. Keyword : market orientation, network, dan performance